2010
DOI: 10.4103/0019-509x.63006
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone hormone receptor status in breast carcinoma: Comparison of immunocytochemistry and immunohistochemistry

Abstract: Although Immunocytochemistry removes the derogatory step of antigen deterioration, technical errors can cause hindrance in achieving the best of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 3 publications
1
28
1
Order By: Relevance
“…Several authors have reported similar results previously, and Radhika et al . have shown a congruence of positive and negative cases as low as 50% for ER and 29% for PR …”
Section: Discussionmentioning
confidence: 91%
“…Several authors have reported similar results previously, and Radhika et al . have shown a congruence of positive and negative cases as low as 50% for ER and 29% for PR …”
Section: Discussionmentioning
confidence: 91%
“…The possibility of using routinely prepared direct smears for subsequent ICC staining is very important in cytopathology, especially in cases of very scarce FNA samples, or when the samples were not adequately prepared for immunocytochemistry at the time of performing FNA. Unfortunately, ICC assessment of ER status on direct smears showed the widest range of concordance with standard IHC assessment on FFPET, from 50% to up to 95% …”
Section: Discussionmentioning
confidence: 99%
“…According to published studies, FNA samples processed as cell blocks, direct smears, cytospins or liquid‐based cytology (LBC) are suitable for the immunocytochemical (ICC) assessment of ER status. However, the concordance between the results obtained on FNA samples and corresponding formalin‐fixed, paraffin‐embedded tissue (FFPET) samples found in these studies varied from as low as 50% to up to 98% . Great variability in concordance, sample processing and slide preparation procedures, with multiple steps that can potentially affect the detection of ERs, makes any comparison and conclusion about the optimal method impossible.…”
Section: Introductionmentioning
confidence: 97%
“…These systems include immunocytochemistry (ICC), immunofluorescence (IF), fluorescence activated cell sorting (FACS), and reverse transcriptase polymerase chain reaction (RT-PCR)-based molecular assays. Most of these assays include a separation by size or biological characteristics, such as the expression of epithelial or cancer cell-specific markers (Moretti et al, 2013;Radhika et al, 2010;Swennenhuis et al, 2013;Van der Auwera et al, 2010). Only one system to detect CTCs in patients with metastatic cancers has been approved by the United States Food and Drug Administration (U.S. FDA).…”
Section: Introductionmentioning
confidence: 99%